Поет на другому березі: поетика афекту у прозі Богдана Ігоря Антонича. Стаття друга - Галета, О. (Слово і Час, 2021)
Стаття становить другу частину дослідження, у якому недописаний
роман Богдана Ігоря Антонича «На другому березі» розглядається із
перспективи генетичної критики як приклад авантексту, укладеного на
основі чернеток, що фіксують процесуальність письма. На підставі рукопису проаналізовано не відображені у виданнях основні типи текстових
змін як свідчення «поетики стану», що виводить письмо за межі дихотомій суб’єкта й об’єкта, Ероса й Танатоса, людського й не-людського —
за рамки індивідуалізму і самої мови, у сферу інтерсуб’єктного та інтермедійного. Поступаючись розвитком дії супроти інтенсивності стану, проза Антонича свідчить про формування афективної поетики і нового
типу модерної чуттєвості та відповідної практики письма. This is the second paper of the two-part study examining the ‘unwritten novel’ “On the
Other Bank” by Bohdan Ihor Antonych, a notable Western Ukrainian writer of the interwar period. Known primarily for his poetry, Antonych did not finish this novel-in-progress,
leaving behind only draft notes, that offer a glimpse into the very process of his writing.
Analyzed from the perspective of genetic criticism, Antonych’s manuscripts are treated as an
avant-text, demonstrating a ‘scenario of writing’ in the transition from the novel of action
to the novel of state.
In contrast to his image-based poetry Antonych’s prose rests on the technique of description.
Depicting nature or the urban environment, the author conveys a certain emotional
and psychological condition. Paying special attention to qualitative adjectives, he
appeals to the sensory experience of the reader. Despite the fact that the plan of the novel
indicates the main events of the plot, the author mainly captures the emotions of the characters.
Dialogues also play an unusual role in the text, as their function is expressive rather
than a communicative one.
Since the dynamics of the text is based on emotional and psychological movement, and
not on the sequence of events or judgments, it is considered to be an example of affective
poetics in Ukrainian modern literature. Affect appears in Antonych’s text as force and tension.
It shapes the human personality and at the same time challenges it. Affect goes beyond
discursiveness and captures the body; its intensity is expressed through the voice and speed.
Antonych’s characters share a common transpersonal experience in their childhood and a
common object of desire aft er becoming adults. Moreover, the transfer of emotions into the
sphere of interpersonal relations gives the affect not only a psychological but also an ethical
dimension.
Analyzing Antonych’s manuscript, the author of the paper focuses on the dynamics of
writing, not on the one of the plot, and finds grounds for conclusions about the affective
nature of Antonych’s prose. It is evident that in the ‘unwritten novel’ “On the Other Bank”
Antonych depicts the modernist type of literary character as homo sentiens, who perceives
the world in a subtle way and experiences it deeply.